AISF position paper on HCV in immunocompromised patients. Issue 1 (January 2019) - ,; Marzano, Alfredo; Angelucci, Emanuele; Astegiano, Marco; Baratelli, Chiara; Biancone, Luigi; Bironzo, Paolo; Brancaccio, Giuseppina; Brunetto, Maurizia Rossana; Bruno, Raffaele; Burra, Patrizia; Cabras, Maria Giuseppina; et al.
Abstract: This report summarizes the clinical features and the indications for treating HCV infection in immunocompromised and transplanted patients in the Direct Acting Antiviral drugs era.